« Avons-nous donc tellement besoin de démons ? » Voyageurs français du xxe siècle à Bali - Gilles Louÿs (Viatica)
This article studies the reactions of travellers Henri Michaux and Antonin Artaud faced with the artistic practices of Bali. Artaud, an experienced traveller, was confronted with the revelation of a total theatre experience during a Balinese show in Paris in 1931: he then postulated a kind of universality of theatre. Michaux, who visited Bali in the years 1930-1931, had a more culturalist and less informed view of it because, although he was aware of the idiosyncrasy of Balinese art, he lacked in-depth cultural references on the subject.